Determinants of Business Resilience in Small and Medium Enterprises in Pekalongan: Business Process Capability as a Mediating Variable - Sulthoni, Muhammad; Winarto, Wahid Wachyu Adi; Adinugraha, Hendri Hermawan; Sadali, Ayatullah; Rahmawati, Ferida (Bina Nusantara University, 2024)
The purpose of this article is to investigate the model of how business process skills, through system adoption, affect business resilience and performance. empirical research on small and medium-sized businesses that currently run their operations using ERP systems. The adoption of accounting information systems is shaped by the use of business intelligence, the deployment of dynamic accounting information systems, and human resource competences associated with the use of accounting information systems. Additionally, the adoption of accounting information systems and organizational resilience are moderated by business process capabilities. One way to get empirical data is through surveys. Path analysis was conducted using partial least squares. Information systems adoption as a foundation for enhancing organizational resilience, including the use of business intelligence, resource competences associated with accounting information system use, and dynamic accounting information system deployment. As a mediating variable, business process capability has the power to boost business resilience, which will enhance organizational performance. Creation of ideas that serve as a foundation for assessing organizational performance and resilience models through the use of accounting information systems in business processes.